2015
DOI: 10.3945/jn.114.205674
|View full text |Cite
|
Sign up to set email alerts
|

Purified Anthocyanin Supplementation Reduces Dyslipidemia, Enhances Antioxidant Capacity, and Prevents Insulin Resistance in Diabetic Patients1–3

Abstract: These findings demonstrate that anthocyanin supplementation exerts beneficial metabolic effects in subjects with type 2 diabetes by improving dyslipidemia, enhancing antioxidant capacity, and preventing insulin resistance. This trial was registered at www.clinicaltrials.gov as NCT02317211.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
252
3
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(283 citation statements)
references
References 51 publications
11
252
3
17
Order By: Relevance
“…In a clinical trial of 24 weeks involving 58 diabetic patients, the subjects in the anthocyanin group consumed two anthocyanin capsules (160 mg anthocyanins) twice daily purified from bilberry and blackcurrant [86]. The results show that anthocyanin group had a significantly lower fasting plasma glucose and insulin resistance index, as well as significantly elevated serum adiponectin and β-hydroxybutyrate concentrations compared to the placebo supplementation.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…In a clinical trial of 24 weeks involving 58 diabetic patients, the subjects in the anthocyanin group consumed two anthocyanin capsules (160 mg anthocyanins) twice daily purified from bilberry and blackcurrant [86]. The results show that anthocyanin group had a significantly lower fasting plasma glucose and insulin resistance index, as well as significantly elevated serum adiponectin and β-hydroxybutyrate concentrations compared to the placebo supplementation.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…A recent study of Chinese patients with T2DM reported that 24-week supplementation with 160 mg/day anthocyanins from bilberries and blackcurrants lowered fasting plasma glucose and HOMA-IR [40]. Furthermore, Novotny et al [15] noted in an 8 week intervention with overweight, older adults that low calorie cranberry juice (240 mL/ day) reduced fasting glucose and improved HOMA-IR in individuals with a high baseline value.…”
Section: Glucoregulationmentioning
confidence: 99%
“…Também há ativação de NADPHoxidases, culminando na produção de espécies reativas de oxigênio, que por sua vez, aumentam a formação de produtos avançados de glicação. Neste contexto haverá ativação de fator nuclear-kappa B que ativa a transcrição de citocinas pró-inflamatórias, como a IL-6 e o peptídeo-1 quimiotático de monócitos, intensificando a resposta inflamatória [20,[24][25].…”
Section: /7unclassified
“…Esta é uma das razões pelas quais há níveis anormais de lipídeos na resistência à insulina. Elevados níveis de lipoproteína de baixa densidade ligada ao colesterol (LDL-c) e baixos níveis de HDL-c, além de aumentos nos níveis de proteína C reativa, também se relacionam com os radicais livres em diferentes estudos [29][30][31][32][33].…”
Section: /7unclassified